Representativeness of Black Patients in Cancer Clinical Trials Sponsored by the National Cancer Institute Compared With Pharmaceutical Companies. Issue 4 (24th April 2020) - Unger, Joseph M; Hershman, Dawn L; Osarogiagbon, Raymond U; Gothwal, Anirudh; Anand, Seerat; Dasari, Arvind; Overman, Michael; Loree, Jonathan M; Raghav, Kanwal
Abstract: Background: Many clinical trials supporting new drug applications underrepresent minority patients. Trials conducted by the National Cancer Institute's National Clinical Trial's Network (NCTN) have greater outreach to community sites, potentially allowing better representation. We compared the representation of Black patients in pharmaceutical company–sponsored cancer clinical trials with NCTN trials and with the US cancer population. Methods: We established a large cohort of study publications representing the results of trials that supported new US Food and Drug Administration drug approvals from 2008 to 2018. NCTN trial data were from the SWOG Cancer Research Network. US cancer population rates were estimated using Surveillance, Epidemiology, and End Results survey data. We compared the proportion of Black patients by enrollment year for each cancer type and overall. Tests of proportions were used. All statistical tests were 2-sided. Results: A total 358 trials (pharmaceutical company–sponsored trials, 85; SWOG trials, 273) comprised of 93 825 patients (pharmaceutical company–sponsored trials, 46 313; SWOG trials, 47 512) for 15 cancer types were analyzed. Overall, the proportion of Black patients was 2.9% for pharmaceutical company–sponsored trials, 9.0% for SWOG trials, and 12.1% for the US cancer population ( P  < .001 for each pairwise comparison). These findings were generally consistent across individual cancer types. Conclusions: The poor representation of Black patients in pharmaceutical company–sponsored trials supporting new drug applications could result in the use of new drugs with little data about efficacy or side effects in this key population. Moreover, because pharmaceutical company–sponsored trials test the newest available therapies, limited access to these trials represents a disparity in access to potential breakthrough therapies.